Microstructure and mechanism of silicanizing process on mild steel substrate using tronoh silica sand at 1000 Â°c for 4 h - Yunos, Y.F.M. (Springer Science and Business Media Deutschland GmbH, 2020)
This paper presented a new route of producing coating onto a mild steel substrate called âSilicanizingâ by using natural silica sand originated from Tronoh Silica Sand (TSS) at elevated temperatures. Influence of the silicanizing process parameters especially temperature and time on the silicanized coating layerâs microstructure and mechanism were studied. Formation of Fe-SiO2 via interdiffusion of Fe and SiO2 were determined by the rate of grain boundary diffusion of SiO2 through the growing Fe-SiO2 phase shown at Silicanizing process temperature of 1000 Â°C for 4 h. Relevant silicanizing mechanism and chemical reaction involved in transforming TSS particles into thin film silicanized-coating on mild steel substrate is expected to be established. Â© Springer Nature Singapore Pte Ltd. 2020.